Do Board Traits Influence Firms’ Dividend Payout Policy? Evidence from Malaysia - Tahir, Hussain; Rahman, Mahfuzur; Masri, Ridzuan (Korea Distribution Science Association (KODISA), 2020)
The study aims to investigate factors that determine dividend payout policy using 336 non-financial firm year observations covering the period 2005 to 2016 in Malaysia. We found a significant positive relationship between corporate board size, board members average age, board tenure and dividend payout policy. We also found a strong negative effect and statistically insignificant relationship of board diversity, board independence, CEO duality and dividend payout policy. Additional, financial leverage has a negative effect on dividend payout policy. It is also noticed that firms with diverse boards are more likely to pay dividends and tend to pay larger dividends than those with non-diverse boards. Our results suggest that board diversity has a significant impact on dividend payout policy. Impact of board diversity on dividend payout policy is particularly conspicuous for firms with potentially greater agency problems. Our findings are consistent with the argument that corporate board traits enhancement positively affect the dividend payout policy which is beneficial for shareholders. This study offers useful insights into the current global debate on board traits and its implications for firms. The dividend payout policy signals good news to investors. Corporate board traits and firm's financial decision are the factors that disrupt the dividend decision. © The Author(s).